EFEKTIVITAS PENGGUNAAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA KETERAMPILAN MEMBACA PEMAHAMAN TEKS BIOGRAFI SISWA KELAS VII SMP NEGERI 1 JETIS BANTUL - Dwi Apriliya Putri; Wijaya Heru Santosa (Universitas Sarjanawiyata Tamansiswa, 2017)
The Effectiveness Of Using Cooperative Integrated Reading Composition (CIRC) Model InÂ Reading Skill Of Biography Text Comprehension The Students Grade VII SMP N 1 Jetis Bantul. The purpose of this research is to prove the effectiveness of usingÂ Cooperative Integrated Reading and Composition (CIRC)Â in learning model than the using communicative method in reading biography text comprehension. This research did in SMP N 1 Jetis Bantul. The kind of research is Quasi-Experimental with the population of 192 students. The sample with cluster random sampling. Grade VII F is to experiment, and grade C is to class control. The analysis technique with t-test, normality test and homogeneity test. The result of this research shows that there is a significant effect on the achievement of reading biography text using CIRC model than the achievement of reading biography text using the communicative method.